Dalbavancin (BI-387) for the treatment of complicated skin and skin structure infection. Issue 2 (February 2014) - Leuthner, Kimberly D; Yuen, Angela; Mao, Yu; Rahbar, Aryan
<x xml:space="preserve">Abstract</x> In the era of increasing antibiotic resistance, development of new agents that could provide therapeutic options for difficult to treat pathogens is vital. Dalbavancin is a new lipoglycopeptide recently approved by the US FDA for the treatment of acute bacterial skin and skin structure infections. A derivative of the older glycopeptide class, chemical structure alterations resulted in a molecule with a similar mechanism of action, however, with a comparatively increased activity as reflected by organism MICs. These modifications also resulted in an antibiotic with distinctive properties that allow for once-weekly dosing in the treatment of Gram-positive pathogens, including methicillin-resistant Staphylococcus aureus and drug resistant Streptococcus spp. As the first of these long acting compounds, understanding the pharmacokinetic and pharmacodynamic properties of agents like dalbavancin is essential for determining a place in therapy.